Editorial: moving towards a robust definition of sarcopenia in cirrhosis—authors' reply. Issue 3 (20th January 2019) - Engelmann, Cornelius; Schob, Stefan; Seehofer, Daniel; Berg, Thomas
Abstract : Linked Content This article is linked to Engelmann et al and Sinha papers. To view these articles, visit https://doi.org/10.1111/apt.15026 and https://doi.org/10.1111/apt.15070 .